Após a angústia: sobre propriedade e impropriedade na analítica existencial de Heidegger - Antunes, Ezildo (2017)
Guided by mainly in the book Being and time fom the german phylosopher Martin Heidegger (1889-1976), this book aims to anwer the question: What comes after the anguish? In order to carry out this aim, the work consider the themes from existencial analitic, subproject from the biggest study to know the fundamental ontology. In the subproject in question, Heidegger presentes us the being-there, the entity who comprehends the being and, for that insinuate like privileged being. Seeking for total characterization of this entity, Heidegger is presenting on the pages of the work mentioned, the constitutives structures by himself, nominated of existencial. In the initial chapters of this work, after realizing the preliminar consideration of existencial analitic, we will go to the identification of these existencial. First of all, being-there, stands out about the traditional conception of human being, it is, through out the responsable existence by himself. Thus, the comprehension about this being-there, goes on in existencial seek out of this biggest character to know, being an entity of power-be. In this way, the existentiality of being-there is always in the world to which he was launched, and it is in the world to being-there it will inaugurate its first existential behaviors. From now on in the diverse ways of occupation, being-there, througt out of the use that he does of the tools, will go experienced the entire world to know, the significance. In this way, the being-there is being in the world who will exist in the most of the time improper use, it is in the way of work of the tools, he will experience the totality of the world to know the significance. In this way, the being-there is to being in the world who will go existente in the most of times in order to, it is in the use of anyone object, in the occupations and protected by the dictatorial character of the impersonal. In this way, escape the truth of its existence, it is, the possibility of “recognize” by himself like a being the power-being. The opportunity that this entity beside its existence guided in decadence, has in your constitution nominated affective tone, which will go straight the way as the being-there look himself connected with the world. Among the many affective tones Heidegger presents exactaly in the paragraph forty the Being and time the anguish such as the fundamental affective tone. It has the fundamental character, because he puts the being-there in front of himself, suspend the occupational mobilizers and, more than that, it will be in the anguish crisis that the being-there can rediscover like being the power-being that it is. Passed the anguish crisis, what decision can take the being-there? As we have seen, being-there is an entity of possibilities, that is, even after being suspended before the nothingness that is, through the 'clear night' of anguish, being-there, as a possibility, can decide by the character of impropriety of its existence if, on the one hand, to intensify its existence in the most banal everyday, that is, to submerge himself more and more in the occupations, being guarded by the impersonal and thus always fleeing from the encounter with its own being. On the other hand, if the being-there decided by propriety as a way of existence, he tends to search for the truth of its existence, guided by that who it is in essence: care. Therefore, being-there will develop a careful handle with its own existence, redefine its projects in the authentic way.